2018
DOI: 10.1088/1361-6501/aad771
|View full text |Cite
|
Sign up to set email alerts
|

‘Hi-Fi AFM’: high-speed contact mode atomic force microscopy with optical pickups

Abstract: High-speed atomic force microscopy (HS-AFM) is a powerful emerging technique used to gain insight into real-time nanoscale dynamics and phenomena across the sciences. By performing measurements of material properties, abundancy counting and dimensional analysis, it enables a new generation of discoveries at the atomic scale. Here, we demonstrate the use of an optical pickup unit (OPU) typically found in PCs, Hi-Fis and games consoles worldwide, as a vertical detection system within in a HS-AFM operated in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…To make a compact and thus portable setup, an OPU (HD850, Sanyo) originally for a digital versatile disc (DVD) drive, a piezo actuator (TA0505D24W, Thorlabs), a fabricated micropipette resonator, and a control and readout printed-circuit board (PCB) are assembled with three-dimensional (3D) printed parts, as shown in Figure a. The control and readout PCB along with the OPU performs the following two functions.…”
Section: Methodsmentioning
confidence: 99%
“…To make a compact and thus portable setup, an OPU (HD850, Sanyo) originally for a digital versatile disc (DVD) drive, a piezo actuator (TA0505D24W, Thorlabs), a fabricated micropipette resonator, and a control and readout printed-circuit board (PCB) are assembled with three-dimensional (3D) printed parts, as shown in Figure a. The control and readout PCB along with the OPU performs the following two functions.…”
Section: Methodsmentioning
confidence: 99%
“…Many attempts have been made to use an OPU as a base and apply it to various types of optical devices. For example, previous studies have reviewed its feasibility for use with optical microscopes [ 17 , 18 ] precise devices for determining refractive index at the femtoliter volume level [ 18 , 19 ] and in biosensing (micro or nanoscale biological sensors) [ 20 ], high-speed contact-mode atomic force microscopy [ 21 ], and optical imaging modules for astigmatic detection systems [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various groups recently demonstrated the resolving power of environmental scanning electron microscopy (ESEM) for studying ice nucleation (Kiselev et al, 2016;Wang et al, 2016;Zimmermann et al, 2008). Unfortunately, ESEM is unable to operate under realistic atmospheric pressures and is prone to introducing electron-beam damage and local heating of condensed water (Rykaczewski et al, 2009). Atomic-force microscopy (AFM) is unique among highresolution microscopies in that it nondestructively generates the three-dimensional topography of a surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, a key limitation of most commercial AFMs is their slow imaging speed. Current developments in high-speed AFM (HS-AFM) are encouraging and have the potential to significantly advance heterogenous nucleation research (Ando, 2014;Russell-Pavier et al, 2018) if emerging ice crystals could be observed directly with a ∼ 10 nm resolution, thus improving significantly the accuracy of locating nucleation sites.…”
Section: Introductionmentioning
confidence: 99%